2007
DOI: 10.1007/s11103-007-9168-5
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon-plus Targeting Technology (APTT) for rapid production of a highly unstable vaccine protein in tobacco plants

Abstract: Due to an unfortunate misunderstanding, the co-corresponding author and the electronic supplementary materials were not properly identified in the original publication. The correct representation of the authors and their affiliations is listed below.The online version of the original article can be found at http:// dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(), and in Azhakanandam et al . (); ‘agrodrench’ (drenching the soil under plants) and ‘wound‐and‐spray/agrospray’ methods, respectively, have been described. However, as the successful delivery by Agrobacterium results in systemic viral infection when even very rare or single events of transfection could result in detectable symptoms, the efficiency of Agrobacterium delivery per se remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…(), and in Azhakanandam et al . (); ‘agrodrench’ (drenching the soil under plants) and ‘wound‐and‐spray/agrospray’ methods, respectively, have been described. However, as the successful delivery by Agrobacterium results in systemic viral infection when even very rare or single events of transfection could result in detectable symptoms, the efficiency of Agrobacterium delivery per se remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hypervirulent strains of Agrobacterium, such as the succinamopine-type EHA105 and AGL1, improve transformation efficiencies (Hellens et al, 2000;Zhi et al, 2015), and might increase agro-inoculation success rates. The chrysopinetype strain Chry5 was originally isolated from chrysanthemum (Shao et al, 2018) and its derivative strain CryX was reported to have agro-inoculation efficiencies 100-1000 times higher than those of commonly used Agrobacterium strains ( (Azhakanandam et al, 2007;Giritch et al, 2013;Gleba et al, 2014;Grimsley et al, 1986;Hahn et al, 2015;Krenek et al, 2015). Viruses might be asymptomatic, vertically inherited in host plants and lack cell-to-cell movement (Roossinck, 2010); these aspects should be taken into account during experimental design and result evaluation.…”
Section: and Inoculation Efficiencymentioning
confidence: 99%
“…Both transgenic expression and infection with recombinant viruses have been shown to be efficient systems for the production of foreign proteins in plants (Cañizares et al, 2005;Streatfield, 2007). The transformation of plants with a full-length viral cDNA, which is then transcribed into an RNA that can be amplified by the viral replication machinery ('amplicon'), integrates the stability of the transgenic system with the high copy numbers of viral expression vectors (Azhakanandam et al, 2007). However, constitutive viral replication can cause disease symptoms, impeding the appro- and Baulcombe, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…They frequently yielded low viral accumulation levels, mainly because plants displaying disease symptoms could be counterselected during the transformation process and/or because the amplicon transgene induced an efficient antiviral RNA silencing response (Angell and Baulcombe, 1997; Liu et al ., 2004). Therefore, special strategies, such as the co‐expression of strong silencing suppressors (Mallory et al ., 2002; Azhakanandam et al ., 2007) or the use of chemically controlled promoters (Mori et al ., 2001), have been necessary in order to obtain amplicon lines with high expression levels.…”
Section: Introductionmentioning
confidence: 99%